An Umbrella Surface in \(\mathbb{R}^{3}\) as An Orbit Surface (Journal of Informatics and Mathematical Sciences, 2018)
In this study, an umbrella surface as an orbit surface of an umbrella motion is defined. Matlab applications and some examples are given.
Keywords: Two parametric motion; Motion; Umbrella Surface